The Dermatofibrosarcoma Protuberans In A 13-Year-Old: A Rare Case Of Soft Tissue Sarcoma Of The Skin : A Rare Case Of Soft Tissue Sarcoma Of The Skin - ., Windy Rhomadani Putra; Iskandar, Fery; Dumaria Ketty (Faculty of Medicine, Hasanuddin University., 2023)
Introduction and importance: Dermatofibrosarcoma protuberans (DFSP) is a rare soft tissue sarcoma that primarily affects middle-aged adults but can also occur in children. Despite its low metastatic potential, DFSP displays aggressive local behavior and a high rate of local recurrence. Diagnosis in children can be delayed due to confusion with other skin conditions. This case report aims to discuss the case management of dermatofibrosarcoma protuberans in a 13 year old female. Presentation of case: A 13-year-old female patient presented with a progressively enlarging lump on the left eyelid, initially resembling small brown spots that coalesced over 7 months. Intermittent bleeding and pain were reported. Physical examination revealed a dark brown mass in the left frontotemporal region, with solid, non-fragile characteristics. Clinical diagnosis suggested a suspicious malignant skin tumor, confirmed as basal cell carcinoma. Treatment involved wide excision and flap reconstruction. Post-operative care included infusion, antibiotic injection, and pain management. The patient's prognosis was favorable, though functional impairment was possible. Follow-up revealed histopathological findings of pigmented dermatofibrosarcoma protuberans. Discussion: DFSP is a rare but significant malignancy that poses diagnostic challenges due to its varied clinical presentations and histopathological features. While primarily affecting young to middle-aged individuals, it can also manifest in pediatric populations. Diagnosis typically involves histopathological assessment, confirming characteristic spindle cell proliferation with CD34 expression. Surgical excision remains the cornerstone of treatment, complemented by adjuvant therapies like imatinib mesylate or radiation in select cases. Regular surveillance, comprising frequent evaluations in the initial post-excision period followed by yearly monitoring, is imperative for detecting any recurrence or metastasis promptly. Conclusions: The structured approach in DFSP ensures optimal patient management and outcomes. Surgical management with Wide local excision (WLE) or Mohs micrographic surgery (MMS) is the gold standard in the treatment of DFSP.